Corporate Responses to Climate Change: Achieving Emissions Reductions Through Regulation, Self-Regulation and Economic Incentives - Sullivan, Rory (Routledge, 2008)
Corporate Responses to Climate Change has been written at a crucial point in the climate change debate, with the issue now central to economic and energy policy in many countries. The book analyses current business practice and performance on climate change, in the light of the dramatic changes in the regulatory and policy environment over the last five years. It will be essential reading for businesses, policy-makers, academics, NGOs, investors and all those interested in how the business sector is and should be dealing with the most serious environmental threat faced by our planet.